2021
DOI: 10.1002/epi4.12456
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis program: Detection of epileptic foci in young children using an adult normative database: Initial experience

Abstract: Objective To report our initial experience using an adult‐template MAP in drug‐resistant focal epilepsy in five children with apparently normal MRI. Methods Patients selected were highly suspicious of harboring focal structural lesions and had negative brain MRI studies. MAP was performed using a locally obtained adult database as a template. Results were reviewed by two neuroradiologists. Pertinence of MAP‐positive areas was confirmed by the focal epileptic hypothesis or by pathology when possible (J Neurorad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was particularly interesting that the MAP for FCD diagnosis might be more applicable with various types of references; for example, a previous pilot study used the MAP and identified FCD in a childhood database using an adult template. 15 However, a well-designed study with a large population is required to obtain ample evidence about the reliable common reference.…”
Section: Discussionmentioning
confidence: 99%
“…It was particularly interesting that the MAP for FCD diagnosis might be more applicable with various types of references; for example, a previous pilot study used the MAP and identified FCD in a childhood database using an adult template. 15 However, a well-designed study with a large population is required to obtain ample evidence about the reliable common reference.…”
Section: Discussionmentioning
confidence: 99%